2002
DOI: 10.1093/oep/54.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Job search methods and outcomes

Abstract: In this paper we investigate the process of job search, using a unique, large-scale data set for Portugal that allows us to assess the effect of job search methods on escape rates from unemployment and, in a new departure, the impact of job-finding methods used by the unemployed on earnings. In each case, the characteristics of workers receive careful attention. In addition, the effectiveness of the job search process is evaluated in terms of the periodicity of the resulting job match. Some emphasis is accorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
1
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(153 citation statements)
references
References 14 publications
(14 reference statements)
6
138
1
8
Order By: Relevance
“…First, in our study job-search intensity was conceptualized as a unitary construct. Since several studies have shown that success in job search depends on the selected search channel (e.g., Addison & Portugal, 2002;Weber & Mahringer, 2008), future research should focus only on particular job search behaviors, and their relationship with reemployment. Second, although we controlled for T1 unemployment, the dynamics of job search and its relationship with re-employment could be influenced by the fact that we included a large proportion of individuals who have been unemployed for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…First, in our study job-search intensity was conceptualized as a unitary construct. Since several studies have shown that success in job search depends on the selected search channel (e.g., Addison & Portugal, 2002;Weber & Mahringer, 2008), future research should focus only on particular job search behaviors, and their relationship with reemployment. Second, although we controlled for T1 unemployment, the dynamics of job search and its relationship with re-employment could be influenced by the fact that we included a large proportion of individuals who have been unemployed for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the wage equation we use a grouped regression model and assume a parametric distribution (lognormal) for the error term. The assumption that the distribution of the error tem is lognormal has been widely adopted in estimating equations using censored wage data (see, for instance, Addison and Portugal, 2002). …”
Section: Methodsmentioning
confidence: 99%
“…Widespread use of friends, relatives and acquaintances to search for jobs is a stylized fact (Rees, 1966;Granovetter, 1974Granovetter, , 1995Holzer, 1988;Blau and Robins, 1990;Montgomery, 1991;Gregg and Wadsworth, 1996;Topa, 2001;Addison and Portugal, 2002;Wahba and Zenou, 2005;Bentolila, Michelacci and Suárez, 2010;Pellizari, 2010).…”
Section: Introductionmentioning
confidence: 99%